Change of sagittal spinal alignment and its association with pain and function after lumbar surgery augmented with an interspinous implant. Issue 1 (December 2017) - Crawford, Rebecca; Malone, Quentin; Price, Roger
Abstract Background Interspinous spacer/implants like the Device for Intervertebral Assisted Motion (DIAM™) are controversially yet commonly used in the surgical treatment of lumbar degenerative pathologies. Criticism is based on ill-defined indications, lack of superiority over decompression, and a poorly understood mechanical effect. Yet, continued use by surgeons implies their perceived clinical merit. We examined radiographic spinal alignment for 12 months, and pain and function for 24 months, after DIAM-augmented surgery to improve the understanding of the mechanical effect relating to clinical outcomes in patients. Methods We undertook a single-surgeon prospective, longitudinal study of 40 patients (20 F, 20 M) who received DIAM-augmented surgery in treatment of their symptomatic lumbar degenerative condition. Outcomes measured included sagittal spinal alignment (lumbar lordosis, sacral inclination, primary (PDA), supradjacent (SDA) disc angles, and regional sagittal balance (RSB; standing lateral radiographs), and back and leg pain (visual analogue scale; VAS) and function (Oswestry Disability Index; ODI). Responders were identified as those with clinically meaningful improvement to pain (>20%) and function (>15%) at 24 months postoperatively; features of sagittal spinal alignment between responders and non-responders were examined. Results Sagittal alignment was unchanged at 12 months. At 6 weeks postoperatively, PDA (mean (SD)) reduced by 2.2° (4.0°;p  < 0.01) and more-so in back pain non-responders (3.8° (3.2°)) than responders (0.7° (4.4°);p  < 0.05). Positive preoperative RSB in responders (26.7Rmm (42.3Rmm); Rmm is a system-relative measure) decreased at 6 weeks (by 3.1Rmm (9.1Rmm)). Non-responders had a negative RSB preoperatively (−1.0Rmm (32.0Rmm)) and increased at 6 weeks (11.2Rmm (15.5Rmm);p  < 0.05). Clinically meaningful improvement for the whole cohort for back pain and function were observed to 24 months (back pain: 25.0% (28.0); function: 15.4% (17.6); bothp  < 0.0001). Conclusions Unaltered sagittal alignment at 12 months was not related to symptoms after DIAM-augmented lumbar surgery. Subtle early flattening at the index disc angle was not maintained. Preoperative and early post-operative sagittal alignment may indicate response after DIAM-augmented surgery for mixed lumbar pathologies. Further investigation toward defining indications and patient suitability is warranted.